Efficacy of Compassion Focused Therapy for Managing Skin Shaming of Acne in Young Women: Compassion Focused Therapy for Managing Skin Shaming of Acne - Khan, Adeela; Bilal, Ahmad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
People are socially evaluated from face as ugly/beautiful. So person with acne isolate themselves from social gathering because of fear of stigmatized as unattractive. This social rejection leads them towards skin shaming of acne. Previous studies were not giving much importance to psychological impact of acne; just dermatological treatment was focus of attention. Objectives: To find a short duration but effective therapy to manage skin shaming of acne in young women. To test the efficacy of Compassion Focused Therapy on managing skin shaming of acne in young women. Methods: The research was an experimental study with sample of 64 young women of 18-25 years. 32 young women are allocated to therapy group and 32 women are allocated to control group. Data were collected at three time intervals of pre-therapy, post-therapy and follow-up. SPSS 21.0 version was used for data analysis. Results: Results clearly indicated significant reduction of skin shaming due to acne of young women from pre-therapy to post-therapy and also from pre-therapy to follow up. When therapy group women data compared with control group women data, conforms our objectives of study that that compassion focused therapy is effective and efficient therapy to manage skin shaming of acne in young women. Conclusion: Compassion Focused Therapy is successful therapy to manage skin shaming of acne in young women.